IMPROVING STUDENTS’ SPEAKING SKILL THROUGH PICTURES AT 10th GRADE SMK SMART AR-RAHMAN BEKASI - Assakinah, Siti Tsuhaibatu; Nurhendi, Nurhendi (Jurnal Web Informatika Teknologi, 2022)
Language plays a crucial role in our daily lives. Language is very important to how we live. Every day, we engage in conversation and respond to other individuals. English plays a significant role as a global language because it is frequently used for worldwide communication. For those who don't want to be left behind by science and technology, mastering English becomes one of the most crucial things. The purpose of this study was to better understand how picture series can be used as a media education approach to help students develop their speaking abilities. This approach was used this study employed the classroom action research methodology over the course of two cycles. A topic or students in the 10th grade at SMK Smart Ar-Rahman in Bekasi made up the study's participants. Researchers compile information from student test scores on how an image was used to illustrate its meaning. Additionally, information was gathered through learning-related observations. The utilization of graphics has an impact on pupils' ability to learn, according to the research findings that the researchers came to. After using pictures as a speaking skill medium, their speaking skills improved.